Analysis of Leading Food Crop Commodities in Central Sulawesi Regencies/Cities in 2017-2021 - Armin Muis; Muhtar Lutfi; Nurananingsih Nurnaningsih; Ika Rafika (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2022)
Abstracts This research analyzes the superior and competitive food crop commodities in Central Sulawesi from 2017 to 2021. Methods used include Static Symmetric Location Quotient, Dynamic Symmetric Location Quotient, Shift Share Analysis, and Overlay. The data used are secondary data on food crop production obtained from the BPS website and agricultural offices in all districts and cities in Central Sulawesi. The analysis reveals the following leading commodities: rice in Toli Toli Regency, corn in Banggai Islands Regency, soybeans in Morowali, Poso, Donggala, Tojo Una - Una, and North Morowali Regencies, mung beans in various regions, cassava in Donggala, Tolitoli, Buol, and Parigi Moutong Regencies, and sweet potatoes in various regions. The competitive commodities include corn, soybeans, peanuts, and sweet potatoes in several districts. The leading and competitive commodities are corn in Banggai Islands and Poso Regencies, soybeans in Morowali, Poso, and Donggala Regencies, peanuts in Donggala and Tolitoli Regencies, and sweet potatoes in Morowali and Poso Regencies..